Cultivating Tomorrow's Workforce: Indicators of Manpower Potential in Vocational Education - Boonsri, Sukanya; Khuanwang, Watcharaporn; Penphu, Withawat; Punsawai, Pranom; Jermtaisong, Rossarin; Sawetmethikul, Pakornkiat (Journal of Technical Education and Training, 2025)
Developing the potential of manpower in the education sector is an important issue for raising the quality of vocational education and preparing students for the labor market. Therefore, having trustworthy and effective indicators is crucial for assessing and enhancing student learning outcomes. This research, therefore, focuses on developing and examining the construct validity of the indicators of manpower potential outcomes in the education sector of students at vocational education institutions. The sample consists of 471 vocational college students in Thailand, obtained by a simple random method. Data were collected using a questionnaire and analyzed using confirmatory factor analysis. The results show that the indicator consists of 3 components and 16 indicators: knowledge (3 indicators), skills (5 indicators), and characteristics (8 indicators). Examination of construct validity revealed that the model was consistent with empirical data (χ² = 82.57, p = .069, df = 65, χ²/df = 1.270, GFI = .978, RMSEA = .023). All indicators are statistically significant at the .01 level and have standardized component weight values between .674 and .882.